Niederländische Kolonisten in Ungarn in der Arpad-Ära - Pósán, László (Acta Neerlandica, 2017)
Settlers from the Low Countries in the Árpád Age in Hungary In Hungarian documents from the 11th and 13th century we can frequently find the name “flandrenses”, which refers to the settlers coming from the Low Countries and from territories where the Low-Frankish dialect was spoken. They moved in a larger number to South-Transylvania in the middle of the 12th century, during the reign of King Géza II. In the 12th century a huge number of these settlers settled down along the southern borders, in Syrmia. The Byzantine chronicler, Nicetas Choniates, called this territory Frangokhorion: the Land of the Franks. Beside the Flemish-Low-Frankish speaking people, settlers from the neo-Latin territories came to Hungary in the Árpád Age, too. These people were called in the documents “latinus” or “gallicus”, just like the people coming from Italy or France. Above all, “latini” from Wallonia and Low-Lothringia came to Hungary. It is interesting that the neo-Latin speaking settlers settled down dispersed almost everywhere in the country, but the Flemish (German) people took root in bigger ethnical homogenic blocks in their new home. The main reason why people from the far Low Countries and their wider area came to Hungary in the Middle Ages was the existential crisis caused by extreme weather conditions in their old homeland, but the news about fertility of the ground and the wealth of natural resources also attracted them to Hungary.